Microcin MccI47 selectively inhibits enteric bacteria and reduces carbapenem-resistant Klebsiella pneumoniae colonization in vivo when administered via an engineered live biotherapeutic. (31st December 2022) - Mortzfeld, Benedikt M.; Palmer, Jacob D.; Bhattarai, Shakti K.; Dupre, Haley L.; Mercado-Lubio, Regino; Silby, Mark W.; Bang, Corinna; McCormick, Beth A.; Bucci, Vanni
ABSTRACT: The gastrointestinal (GI) tract is the reservoir for multidrug resistant (MDR) pathogens, specifically carbapenem-resistant (CR) Klebsiella pneumoniae and other Enterobacteriaceae, which often lead to the spread of antimicrobial resistance genes, severe extraintestinal infections, and lethal outcomes. Selective GI decolonization has been proposed as a new strategy for preventing transmission to other body sites and minimizing spreading to susceptible individuals. Here, we purify the to-date uncharacterized class IIb microcin I47 (MccI47) and demonstrate potent inhibition of numerous Enterobacteriaceae, including multidrug-resistant clinical isolates, in vitro at concentrations resembling those of commonly prescribed antibiotics. We then genetically modify the probiotic bacterium Escherichia coli Nissle 1917 ( EcN ) to produce MccI47 from a stable multicopy plasmid by using MccI47 toxin production in a counterselection mechanism to engineer one of the native EcN plasmids, which renders provisions for inducible expression and plasmid selection unnecessary. We then test the clinical relevance of the MccI47-producing engineered EcN in a murine CR K. pneumoniae colonization model and demonstrate significant MccI47-dependent reduction of CR K. pneumoniae abundance after seven days of daily oral live biotherapeutic administration without disruption of the resident microbiota. This study provides the first demonstration of MccI47 as a potent antimicrobial against certain Enterobacteriaceae, and its ability to significantly reduce the abundance of CR K. pneumoniae in a preclinical animal model, when delivered from an engineered live biotherapeutic product. This study serves as the foundational step toward the use of engineered live biotherapeutic products aimed at the selective removal of MDR pathogens from the GI tract.